Barrett's Esophagus and Adenocarcinoma - Z.W. Li; A.B.R. Thomson (Canadian Journal of Gastroenterology)
As association between Barrett's esophagus and adenocarcinoma of the esophagus is relatively frequent. Survival with adenocarcinoma is generally poor. Routine surveillance endoscopy is suggested with generous biopsy material and brush cytology to detect either high grade dysplasia or intramucosal carcinoma in patients with Barrett's esophagus. Individual cases of high grade dysplasia should be independently confirmed by another pathologist familiar with dysplasia grading. Esophagectomy should be recommended for those patients with high grade dysplasia whose risk for surgery is outweighed by the possible presence or development of cancer.